Harm perceptions of electronic cigarettes and nicotine: A nationally representative cross-sectional survey of young people in Great Britain. (1st November 2018) - East, Katherine; Brose, Leonie S.; McNeill, Ann; Cheeseman, Hazel; Arnott, Deborah; Hitchman, Sara C.
Highlights: Two thirds (63%) had accurate harm perceptions of e-cigarettes. Few (9%) had accurate harm perceptions of nicotine. Accurate harm perceptions of e-cigarettes and nicotine were positively associated. E-cigarette users, but not smokers, had more accurate e-cigarette harm perceptions. Neither smoking nor e-cigarette use were associated with nicotine harm perceptions. Abstract: Background: E-cigarettes often contain nicotine without the most harmful constituents of tobacco smoke. Aims: This study aims to assess prevalence and correlates of accurately perceiving e-cigarettes as less harmful than cigarettes and that none or a small amount of the harm from smoking comes from nicotine. Methods: Cross-sectional survey of 2, 103 11–18-year-olds in Great Britain in 2016. Prevalence of e-cigarette and nicotine harm perceptions were calculated. Logistic regressions assessed associations between accurate e-cigarette and nicotine harm perceptions and smoking, e-cigarette use, gender, age, region, social grade, family smoking, family e-cigarette use, smoking friends, public approval of smoking, and public approval of e-cigarettes. Associations between accurate e-cigarette and nicotine harm perceptions were also assessed. Results: Most (63.4%) accurate e-cigarette harm perceptions were higher among those aged 16+ (OR = 1.89 [95%CI = 1.45–2.47]), 14–15 (OR = 1.29 [1.00–1.65]), who tried/used an e-cigarette sometimes (OR = 1.51 [1.03–2.21]), with family e-cigarette use (OR = 2.11 [1.46–3.04]), who perceived public disapproval of smoking (OR = 2.11 [1.18–3.77]) and approval of e-cigarettes (OR = 2.44 [1.73–3.45]), and with accurate nicotine harm perceptions (OR = 2.05 [1.28–3.28]). Accurate nicotine harm perceptions were higher among those aged 16+ (OR = 2.60 [1.62–4.16]), from North England (OR = 1.87 [1.02–3.43]) and Wales/Scotland (OR = 2.61 [1.35–5.03]) vs. London, with family smoking (OR = 1.59 [1.05–2.42]), and with accurate e-cigarette harm perceptions (OR = 2.12 [1.32–3.41]). Conclusions: Many young people have inaccurate harm perceptions of e-cigarettes and nicotine. Accurate e-cigarette and nicotine harm perceptions were associated with one another. E-cigarette use was associated with accurate e-cigarette but not nicotine harm perceptions; smoking was not associated with either.